2017
DOI: 10.1002/jbmr.3121
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bone Health in Patients With Type 1 Gaucher Disease Using Impact Microindentation

Abstract: Gaucher disease (GD), one of the most common lysosomal disorders (a global population incidence of 1:50,000), is characterized by beta-glucocerebrosidase deficiency. Some studies have demonstrated bone infiltration in up to 80% of patients, even if asymptomatic. Bone disorder remains the main cause of morbidity in these patients, along with osteoporosis, avascular necrosis, and bone infarcts. Enzyme replacement therapy (ERT) has been shown to improve these symptoms. This cross-sectional study included patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…(18) Our results are also consistent with studies that have shown BMSi to be lower in select patient populations with known skeletal fragility, including those with a history of bone stress injury, (25) type 2 diabetes, (9)(10)(11) HIV, (12) acromegaly, (13) and Gaucher's disease. (14) Our study is the first to examine BMSi in patients with DRFs and is the first to suggest a relationship between occurrence of DRF and BMSi that is independent of femoral neck aBMD. This observation is meaningful, because hip aBMD is commonly used in clinical practice to estimate fracture risk.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…(18) Our results are also consistent with studies that have shown BMSi to be lower in select patient populations with known skeletal fragility, including those with a history of bone stress injury, (25) type 2 diabetes, (9)(10)(11) HIV, (12) acromegaly, (13) and Gaucher's disease. (14) Our study is the first to examine BMSi in patients with DRFs and is the first to suggest a relationship between occurrence of DRF and BMSi that is independent of femoral neck aBMD. This observation is meaningful, because hip aBMD is commonly used in clinical practice to estimate fracture risk.…”
Section: Discussionmentioning
confidence: 75%
“…(6)(7)(8) Although the precise mechanical properties reflected by impact microindentation remain to be established, recent studies using the technique have shown cortical bone properties measured in vivo at the tibial diaphysis to be worse in select patient populations with known skeletal fragility, including those with type 2 diabetes, (9)(10)(11) human immunodeficiency virus (HIV), (12) acromegaly, (13) and Gaucher's disease. (14) Notably, cross-sectional studies have shown that impact microindentation at the tibia diaphysis discriminates individuals with a history of fragility fracture in some, (15)(16)(17) but not all, studies. (18) These studies enrolled subjects with different types of fractures, which may have contributed to the discrepant findings.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies included patients with endocrine disorders such as diabetes mellitus and acromegaly (n = 8) (36,41,48,49,(62)(63)(64)(65). Six studies focused on patients having sustained fragility or stress fractures (33-35, 38, 50, 55), three studies evaluated BMSi outcomes in patients receiving osteoporosis treatment (37,44,68) and another three studies reported on patients with a rare metabolic bone disorder: Type 1 Gaucher Disease, Paget's and Camurati-Engelmann disease (57,60,67). Seven studies, two of which included patients with diabetes mellitus (41,63), were performed in two population-based cohorts from Sweden and Australia, both designed to assess epidemiological data in osteoporosis (39,43,51,54,69).…”
Section: Characteristics Of Studies Generated By the Searchmentioning
confidence: 99%
“…Though the mechanisms driving reduced BMSi in diabetics are unclear, the changes BMSi has been associated with the accumulation of advanced glycation end products (AGEs) in human bone 33 and may be the putative mechanism for the fragility observed in T2D. BMSi has also been reported in other clinical morbidities, including chronic kidney disease and transplantation 45 , acromegaly 46 , Paget’s disease 47 , Camurati-Engelmann disease, Type 1 Gaucher disease 48 , and obesity 49 , with BMSi observed to be lower in the respective pathological cohorts.…”
Section: Osteoprobe Studiesmentioning
confidence: 99%